2011
DOI: 10.1136/oemed-2011-100317
|View full text |Cite
|
Sign up to set email alerts
|

Case-based e-learning to improve the attitude of medical students towards occupational health, a randomised controlled trial

Abstract: Objectives Undergraduate medical teaching in occupational health (OH) is a challenge in universities around the world. Case-based e-learning with an attractive clinical context could improve the attitude of medical students towards OH. The study question is whether case-based e-learning for medical students is more effective in improving knowledge, satisfaction and a positive attitude towards OH than non-case-based textbook learning. Methods Participants, 141 second year medical students, were randomised to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…Similar results have been found in a number of studies on CBL in the field of occupational medicine (OM) (Radon et al 2006;Braeckman et al 2009;Kolb et al 2009;Smits et al 2012). OM is concerned with ensuring that workplaces and work practices are safe and not detrimental to employees' health.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results have been found in a number of studies on CBL in the field of occupational medicine (OM) (Radon et al 2006;Braeckman et al 2009;Kolb et al 2009;Smits et al 2012). OM is concerned with ensuring that workplaces and work practices are safe and not detrimental to employees' health.…”
Section: Introductionsupporting
confidence: 76%
“…Students taking part in the NetWoRM project (Net-based training for Work-Related Medicine) enjoyed working on e-learning cases as an add-on to their traditional teaching (Radon et al 2006;Kolb et al 2009). Smits et al 2012 found that online cases to improve the attitude of medical students towards occupational health, resulted in similar changes in knowledge and satisfaction as text-based learning. In another study, the efficacy of CLB in teaching OM was as good as workplace visits as evaluated by student self-reports (Braeckman et al 2009).…”
Section: Practice Pointsmentioning
confidence: 75%
“…Smits and colleagues compared case-based learning and traditional text-based learning in medical education and found no difference in student knowledge between the 2 teaching methods. 11 Another study evaluating the efficacy of case-based computer modules did find improvements in short-term knowledge, but the improvement was not maintained longterm. 12 In pharmacy education, Romero and colleagues reported enhanced student learning in a pharmaceutics course that used case-based learning, but the observation was based on a positive correlation between case study grades and course examination scores.…”
Section: Discussionmentioning
confidence: 99%
“…Strong objective evidence is lacking. [10][11][12][13][14][15][16] At the Feik School of Pharmacy, Applied Pharmacy Care is a series of 6 courses that focuses on the application of pharmaceutical care principles, pharmaceutical knowledge, and professional techniques to solve patient-and medication-related issues. 17 Health literacy had been taught in only 1 course, Applied Pharmacy Care II, to first-year (P1) pharmacy students.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire was based on and adapted from previous works (Smits et al, 2012;Bhardwaj et al, 2015). In designing the questionnaire we started from the idea of what we like to know from our students and it consists mainly in two parts: some demographic data and the research data.…”
Section: Methodsmentioning
confidence: 99%